The carbon emission reduction effect of smart agricultural policy—evidence from China - Zhang, Zheng; Jiang, Shu; Shen, Bing; Mei, Yuan Yuan; Zhang, Xia Ran (Frontiers in Sustainable Food Systems, 2024)
BackgroundAgricultural activities are the second largest source of its greenhouse gas emissions in China, making it imperative to prioritize the reduction of carbon emissions in agriculture to achieve carbon neutrality. Agricultural modernization is recognized as a key strategy for achieving this reduction. In response, China has introduced a smart agriculture policy to catalyze the progress of agricultural modernization. However, it is not clear that the policy will achieve agriculture carbon reductions.PurposeTo examine the impact and mechanism of smart agriculture policy on agricultural carbon emissions, thereby facilitating the transition toward low-carbon practices in agriculture.MethodsUsing panel data across China’s 31 provinces from 2001 to 2020, this paper applies a multi-period differences-in-differences (DID) method to assess the impact and mechanisms of the smart agriculture policy on carbon reduction.Results① The smart agriculture policy exerts a significant positive influence on reducing agricultural carbon emission. ② The policy’s effectiveness is particularly notable in China’s central and western regions and non-grain producing areas, in contrast to the limited impact observed in the eastern provinces and grain-producing areas. ③ Smart agriculture policies have greatly reduced agricultural carbon emissions by promoting the agricultural-scale operation and the advancement of agricultural technology.ConclusionThe paper reveals that smart agriculture policy has a positive effect on carbon emission reduction and provides relevant policy recommendations for the government. This has considerable implications for promoting sustainable agriculture.